If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3K + 11 = 2 Reorder the terms: 11 + 3K = 2 Solving 11 + 3K = 2 Solving for variable 'K'. Move all terms containing K to the left, all other terms to the right. Add '-11' to each side of the equation. 11 + -11 + 3K = 2 + -11 Combine like terms: 11 + -11 = 0 0 + 3K = 2 + -11 3K = 2 + -11 Combine like terms: 2 + -11 = -9 3K = -9 Divide each side by '3'. K = -3 Simplifying K = -3
| 27=1+0.333333333x | | 49-m^2= | | (x-5)(x+3)=-15 | | -3x^2-42x-145=0 | | 14y^2+33y-5=0 | | -5z(z-6)(z+9)=0 | | (3x+4)-6(2x-6)=4x-16 | | 140+2x=1250 | | 1.8T=-72 | | 2x-140=1250 | | 6(3-h)=8h-10 | | 140-2x=1250 | | 9x+2=-7x-126 | | 0.20x+0.05(10-x)=0.10(32) | | 33=N+37 | | d^2-3d=6 | | (2m-5)x^2+mx+7=0 | | -16-p+12=26 | | 45xy-72zw=0 | | 17+2.66=30 | | z+31=26 | | cos(2x+1)=.3 | | cos(2x+1)=5 | | 3.5=x-9.9 | | 2(8)-3(5)+9= | | 3x^2+5=4x+4 | | 12x^2-216x+585=0 | | (8)-3(5)+9= | | 2m+3n=14-n | | 7+x=35 | | 2(x+3)^2=30 | | 0.555555556+0.416666667d=0.916666667+0.777777778d |